1997
DOI: 10.1117/12.267762
|View full text |Cite
|
Sign up to set email alerts
|

Frequency shift and vibronic relaxation of Raman modes in barium nitrate molecular ionic crystal

Abstract: In this paper the results on high resolution spontaneous Raman spectroscopy of barium nitrate molecular ionic crystal at temperature from 8 to 600 K are presented. The temperature dependencies of the linewidth broadening and frequency shifts of internal Raman modes are investigated. The proposed mechanisms of vibronic relaxation of internal Raman modes exhibit low degree of phonon-phonon coupling in the medium. The phonon frequency shifts are found to be due to lattice expansion and are discussed in terms of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
1
2
1
Order By: Relevance
“…(F 1 ), and one translational mode (F 2 ). As can be seen in Figure , the results indicated that all Raman-active modes of PMO/acac (a) and PMO/PVP (b) obtained by the hydrothermal method in this work are characteristic of a tetragonal structure, in agreement with data previously reported in the literature. ,,,, Moreover, the well-defined active-Raman modes suggest that PbMoO 4 are structurally ordered at short range, regardless of the different types of modifiers used during hydrothermal synthesis.…”
Section: Results and Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…(F 1 ), and one translational mode (F 2 ). As can be seen in Figure , the results indicated that all Raman-active modes of PMO/acac (a) and PMO/PVP (b) obtained by the hydrothermal method in this work are characteristic of a tetragonal structure, in agreement with data previously reported in the literature. ,,,, Moreover, the well-defined active-Raman modes suggest that PbMoO 4 are structurally ordered at short range, regardless of the different types of modifiers used during hydrothermal synthesis.…”
Section: Results and Discussionsupporting
confidence: 89%
“…Molybdates and tungstate-based oxides constitute an important class of materials that exhibit various functional properties; in particular, metal molybdates have received special attention due to their novel and intriguing properties for widespread technological applications. Molybdates of relatively large bivalent cations (ionic radius >0.99 Å: Ca, Ba, Pb, Sr) usually exist in the so-called scheelite structure form and have attracted considerable interest due to their promising technological importance in a broad range of applications such as photoluminescence, scintillator materials, humidity sensors, and catalysis . As an important member of this family, lead molybdate (PbMoO 4 ) has gained increasing interest due to its use in a wide range of technological and theoretical fields, , and experimental studies on the optical properties of lead molybdate have been published by different research groups. ,, …”
Section: Introductionmentioning
confidence: 99%
“…This results in the shorter lifetime of vibronic excitation for A g (ν 1 ) modes and broader linewidths , that was found to be 5.6 cm -1 and 6 cm -1 in CaMoO 4 and PbMoO 4 crystals correspondingly. This is in contrary with vibronic relaxation in Ba(NO 3 ) 2 crystal [10] in which the absence of two-phonon splitting relaxation process for A g (ν 1 ) mode results in long vibronic lifetime and narrow mode linewidth (∆ω R = 0.4 cm -1 ). The further investigation of the relaxation mechanisms will help to understand the reasons of A g (ν 1 ) mode narrowing in the range of sheelite tungstates and molybdates with Ca, Sr, Ba and Pb cations.…”
Section: Relaxation Of Raman Modes In Crystalscontrasting
confidence: 66%
“…The temperature dependence of the Raman mode frequencies have been investigated by many authors [4][5][6][7]. It was shown that the Raman frequency can be described by the following expression:…”
Section: Frequency Shift Of Srs-active Modesmentioning
confidence: 99%